Taxonomy of causes, impacts and policy responses to the food price crisis in the Andean region - José Cuesta; Fidel Jaramillo (Inter-American Development Bank, Research Department, 2009)
This paper analyzes the causes, effects and policy alternatives associated with the recent international food price crisis in the Andean region. Additionally, the document makes a first approach to the policy options utilized to confront the crisis, discussing the mix of policies and their potential effectiveness, using a qualitative methodology based in part on schemes proposed in Manzano and Stein (2008), and Malarín (2008). A final section underscores various messages common to the countries of the region. Specifically, the report concludes that this crisis offers a great opportunity for transforming its uncertainties and costs into a stimulus for maturing an infrastructure of prevention and reduction of vulnerabilities in the Andean economies.
Keywords: O20; O18; I30; 330; Food crisis; Distributive impact; Simulation; Compensatory policies; Andean region